2000
DOI: 10.2355/isijinternational.40.224
|View full text |Cite
|
Sign up to set email alerts
|

The Strength and the High Temperature Behaviors of Self-reducing Pellets Containing EAF Dust.

Abstract: The objective of this work was to study the cold and hot behaviors, that is, cold compressive strength, decrepitation, swelling, compressive strength after heating and efficiency of zinc removal of self-reducing pellets containing coal fines and EAF dust. Pellets with 3 and 5 wt% Portland cement, 12 wt% CaCO 3 and without additive were produced. The effect of binder addition on the cold compressive strength was studied during 28 days. For the study of the high temperature behavior, pellets were submitted to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Some of the EAF dust is being disposed of in hazardous waste landfill sites, but because appropriate storage sites are lacking and placed more distant from the generation point, increasing pressure is being placed on steelmakers to adopt some method for the treatment of the dust (Mantovani and Takano, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the EAF dust is being disposed of in hazardous waste landfill sites, but because appropriate storage sites are lacking and placed more distant from the generation point, increasing pressure is being placed on steelmakers to adopt some method for the treatment of the dust (Mantovani and Takano, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, production of DRI by heat treatment might also contribute to significant reduction of Zn, which enables recycling of by-products with low Zn-contents in the blast furnace. [8][9][10][11][12][13] In fact, BOF-sludge and BF-sludge in combination with carbon-containing materials such as BF-dust in agglomerates have not been investigated previously. The possibilities to produce agglomerates with chemical-and physical properties suitable for self-reduction need to be studied.…”
Section: Reduction Behaviour Of Self-reducing Blends Of In-plant Finementioning
confidence: 99%
“…Qingmin MENG, 1) Rufei WEI, 1) Jiaxin LI, 1,3) Ping WANG, 1) Zhifang GAO, 1,2) Zhanxia DI 1) and Hongming LONG 1,2) * The thermal strength characteristics and mechanism of iron ore and carbon pellets (ICP) in the non-isothermal heating process, including the effect of reducing agent, carbon content and heating rate on the thermal strength, were studied by the on-line test device of thermal strength, combined with the TG/DTG-DTA data, the samples microstructure and porosity after reduction. When ICP was damaged by external force at high temperatures, it existed in two states: crush and plastic deformation.…”
Section: Thermal Strength Characteristics and Mechanism Of Iron Ore Amentioning
confidence: 99%
“…Iron ore and carbon pellets (ICP), as a new ironmaking raw materials with good reduction properties, provides some possibilities for the new processes development, such as the production of metallized raw materials, the treatment of steel waste containing Fe and the dressing of complex refractory ore. [1][2][3] Many works have been done referring to the reduction mechanism of ICP [4][5][6][7][8][9][10][11][12][13] and the strength of ICP after reduction, 14,15) providing an important support for the development and application of ICP. Jung et al 4) found the critical temperature of carbon gasification was 1 055°C in the carbothermic reduction of magnetite by TGA-DSC-QMS.…”
Section: Introductionmentioning
confidence: 99%